Advanced Traffic Simulation Framework for Networked Driving Simulators - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (AAC2016 (IFAC), 8th IFAC Symposium on Advances in Automotive Control (AAC 2016))

Modeling Language for Value Networks - Schneider, Marcel; Mittag, Tobias; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, 25th International Association for Management of Technology Conference, Band 25)

Business Model Based Configuration of Value Creation Networks - Mittag, Tobias; Schneider, Marcel; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, Band 25)

Industrie 4.0 - Internationaler Benchmark, Zukunftsoptionen und Handlungsempfehlungen für die Produktionsforschung - Gausemeier, Jürgen; Klocke, Fritz; Dülme, Christian; Eckelt, Daniel; Kabasci, Patrick; Kohlhuber, Martina; Schön, Nico; Schröder, Stephan; Wellensiek, Markus

DESIGN OF A SELF-OPTIMISING PRODUCTION CONTROL SYSTEM - Köchling, Daniel; Gausemeier, Jürgen; Joppen, Robert; Mittag, Tobias (14th International DESIGN Conference)

Integrated and iterative systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Journal of Software Evolution and Process)
The development of software-intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model-based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Strategische Produktplanung - Adaptierbare Methoden, Prozesse und IT-Werkzeuge für die Planung der Marktleistungen von morgen - Gausemeier, Jürgen; Ovtcharova, Jivka; Amshoff, Benjamin; Eckelt, Daniel; Elstermann, Matthes; Placzek, Markus; Wiederkehr, Olga

Value Network Design for Innovations - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Proceedings of the 5th ISPIM Innovation Forum)

Die sich selbst optimierende Lackieranlage - Iwanek, Peter; Kühn, Arno (Journal für Oberflächentechnik 3(56))

Detecting white spots in innovation-driven intellectual property management - Eckelt, Daniel; Dülme, Christian; Gausemeier, Jürgen; Hemel, Simon (International Society for Professional Innovation Management (ISPIM))

Musik - Edition – Medien: Detmolder Projekte Der Digitalen Musikwissenschaft - Richts, Kristina; Röwenstrunk, Daniel

Systematik zur innovationsorientierten Kompetenzplanung - Rübbelke, René

Intelligente Arbeitsvorbereitung in der Cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt Werkstattstechnik online (1/2-2016))
Auf dem Weg zu Industrie 4.0 wird die Arbeitsvorbereitung zunehmend von kognitiver Informationstechnik unterstützt. Der Beitrag präsentiert die bisherigen Ergebnisse des Forschungsprojekts „Intelligente Arbeitsvorbereitung auf Basis virtueller Werkzeugmaschinen“. Projektziel ist eine Cloud-Dienstleistungsplattform zur Reduzierung der Rüst- und Nebenzeiten durch eine intelligente Planung. Hierzu zählen unter anderem die Auswahl und Validierung alternativer Maschinen sowie die automatische Optimierung der Einrichtungsparameter durch verteilte Simulationen.

Instrumentarium für einen lösungsmusterbasierten Entwurf fortgeschrittener mechatronischer Systeme - Anacker, Harald

Systematik zur technologie-induzierten Produkt- und Technologieplanung - Wall, Marina

Systematik zur lösungsmusterbasierten Entwicklung von Frugal Innovations - Lehner, Anne-Christin

Methodik zur Bewertung von Produktionssystemen in der frühen Entwicklungsphase - Rudtsch, Vinzent

Ernährung und psychische Erkrankungen - Libuda, Lars; Antel, J.; Hebebrand, J.; Föcker, M. (Der Nervenarzt)

Strategische Produkt- und Prozessplanung - Gausemeier, Jürgen; Echterfeld, Julian; Amshoff, Benjamin (Handbuch Produktentwicklung)

Systematik zur musterbasierten Entwicklung technologie-induzierter Geschäftsmodelle - Amshoff, Benjamin